Analysis of Land and Building Tax Revenue In Rural and Urban Areas and Its Contribution to Local Original Revenue In West Halmahera Regency - Amira, Wahyuni; Susilo, Danang Djoko; Dariansyah, Deddy (Yayasan Meira Visi Persada, 2025)
Land and Building Tax-Rural and Urban is one of the contributors to Regional Original Revenue in West Halmahera Regency. This research aims to analyze how much Land and Building Tax-Rural and Urban revenue, and how Land and Building Tax-Rural and Urban contributes to Local Original Revenue collected by the Regional Revenue Office of West Halmahera Regency. This study used a qualitative descriptive method with data collection techniques are deep interviews. The results of this research, the contribution of Land and Building Tax-Rural and Urban to Regional Original Income is highest in 2018, and the lowest in 2020. The contribution during 2017 to 2021 is still very lacking with an interpretation value of 2.04%. This research concludes that Land and Building Tax-Rural and Urban revenues in West Halmahera Regency have fluctuated during 2017-2021